Comparison of the effects of modified German volume resistance training versus the traditional method on muscle volume, strength and body composition of active women - Elham Hajivand; Hamid Arazi (فیزیولوژی ورزش و فعالیت بدنی)
Background and Purpose: One of the most important variables affecting the effectiveness of resistance training on muscle strength and hypertrophy is training volume. One of the training methods with a higher volume than the traditional method is the German volume method, which, of course, is more effective. Therefore, the present study aimed to investigate the effect of modified German volume resistance training (RT) compared to the traditional method on hypertrophy, strength and body composition of active women with a history of RT.Materials and Methods: In this study, 24 female athletes with an age range of 20 to 30 years participated voluntarily and were randomly divided into two groups: 12 individuals performed modified German volume RT (the first two movements are 10 sets and the rest of the movements are 3 sets) and 12 individuals conducted traditional RT (all movements 3 sets). Subjects performed 12 weeks of RT with an intensity of 60-75% of one repetition maximum, 3 sessions per week. Before starting the exercise intervention, information about age, height, weight, body composition (muscle mass and fat percentage), hypertrophy and muscle strength were recorded and measured. Measurements were taken before the training period (48 hours before), after the sixth week of the training and finally 48 hours after the last training session.Results: The results of the study showed that both modified German volume RT and traditional method caused a significant increase in the thigh and arm muscles cross-sectional area, upper body and lower body muscle strength and a significant decrease in body fat percentage (P<0.05). However, the changes in the thigh and arm muscles cross-sectional area in both groups and fat percentage in the traditional RT were not significant following 6 weeks (P>0.05). In addition, based on the analysis of variance and between groups comparisons there were no significant differences in the above variables between modified German volume RT and traditional RT after 6 and 12 weeks (P>0.05).Conclusions: In general, considering similar results obtained after both training methods, appears that the German Volume RT has no advantages over traditional RT regarding fat percentage, cross-sectional area of the thigh and arm muscles and the muscle strength of the upper and lower body, although it had a higher training volume. More studies are needed to draw more accurate conclusions in this regard.